Earning My Degree : Memoirs of an American University President. - Gardner, David Pierpont (University of California Press, 2001)
David Pierpont Gardner was president of one of the world's most distinguished centers of higher learning - the nine-campus University of California - from 1983 to 1992. In this remarkably candid and lively memoir he provides an insider's account of what it was like for a very private, reflective man to live an extremely public life as leader of one of the most complex and controversial institutions in the country.